Comparison of Fibreoptic Bronchoscope and C-Mac Video Laryngoscope for Awake Tracheal Intubation with Cervical Spine Immobilization - Tripat Kaur Bindra; Balwinder Kaur Rekhi; Simrit Kaur; Parmod Kumar; PC Zonunmawii (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Awake fiberoptic intubation (AFOI) is a widely accepted technique for managing difficult airways in patients with facial trauma, oropharyngeal masses, and obesity. It preserves the patient’s spontaneous respiratory effort. This study was designed to compare the efficacy of the C-MAC video laryngoscope with a fibreoptic bronchoscope (FOB) in simulated cervical spine immobilization. Methods: This prospective, randomized study included 100 patients aged 18–80 years, with ASA physical status I or II, undergoing elective surgeries requiring cervical spine immobilization. Patients were randomized into two groups: Group I (FOB) and Group II (C-MAC VL). The primary outcome was time to successful intubation and overall success rate. Secondary outcomes included hemodynamic changes and intubation-related complications. Results: The C-MAC group had significantly shorter intubation times compared to the FOB group (p<0.05). No significant difference was observed in the number of attempts between groups (p>0.05). Conclusion: The C-MAC video laryngoscope offers a time advantage over the fibreoptic bronchoscope for awake tracheal intubation in patients with cervical spine immobilization, assuming adequate airway preparation.